Radioactivity amounts, annual effective dose rate, and lifetime cancer risk estimation of some vegetable and fruit samples cultivated in Kahramanmaras, Turkey - Kucukonder, Erdal; Gumbur, Serdar; Sogut, Omer; Dogru, Mahmut (Springer, 2023)
In this research, examples of the fruits and vegetables cultivated in Kahramanmaras, U-238, Th-232, and K-40 levels, were detected, and in the case of consumption of these vegetables and fruits, for several age categories (adults, children (10 years old), and infants), annually effective dose rates and lifetime cancer risks were calculated. In fruit samples, concentrations of U-238, Th-232, and K-40 ranged from under detection limit (UDL) to 15.29 & PLUSMN; 1.14 Bq/kg, 0.30 & PLUSMN; 0.01 to 13.23 & PLUSMN; 1.60 Bq/kg, and 5.82 & PLUSMN; 0.21 to 179.82 & PLUSMN; 1.34 Bq/kg, respectively. The mean concentrations of U-238, Th-232, and K-40 in fruit samples were 5.31 & PLUSMN; 0.44 Bq/kg, 2.72 & PLUSMN; 0.26 Bq/kg, and 56.84 & PLUSMN; 0.57 Bq/kg, respectively. In vegetable samples, concentrations of U-238, Th-232, and K-40 ranged from 0.48 & PLUSMN; 0.04 to 11.77 & PLUSMN; 0.95 Bq/kg, 0.55 & PLUSMN; 0.04 to 4.57 & PLUSMN; 0.44 Bq/kg, and 9.32 & PLUSMN; 0.43 to 52.44 & PLUSMN; 0.52 Bq/kg, respectively. The mean concentrations of U-238, Th-232, and K-40 in the vegetable samples were 6.58 & PLUSMN; 0.65 Bq/kg, 2.72 & PLUSMN; 0.27 Bq/kg, and 27.09 & PLUSMN; 0.27 Bq/kg, respectively. The mean annual effective dose rates for adults, children (10 years old), and infants in fruit samples were 0.184 & PLUSMN; 0.001 mSv/y, 0.288 & PLUSMN; 0.002 mSv/y, and 0.304 & PLUSMN; 0.003 mSv/y, respectively. The average lifetime cancer risks for adults, children (10 years old), and infants in fruit samples were 0.647 & PLUSMN; 0.006 x 10(-4), 1.011 & PLUSMN; 0.010 x 10(-4), and 1.067 & PLUSMN; 0.010 x 10(-4), respectively. The mean annual effective dose rates for adults, children (10 years old), and infants in the vegetable samples were 0.118 & PLUSMN; 0.001 mSv/y, 0.128 & PLUSMN; 0.001 mSv/y, and 0.086 & PLUSMN; 0.001 mSv/y, respectively. The mean lifetime cancer risks for adults, children (10 years old), and infants in vegetable samples were 0.416 & PLUSMN; 0.004 x 10(-4), 0.449 & PLUSMN; 0.004 x 10(-4), and 0.304 & PLUSMN; 0.003 x 10(-4), respectively.
Keywords: Kahramanmaras; Radioactivity in vegetables and fruit; Annual effective dose; The lifetime risk of cancer